Islamic Financial Management Practices and Business Performance in Small Industrial Companies - Abdul Hadi Sirat; Abdul Rahman Jannang (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
This study aims to examine the effect of Islamic financial literacy, investment decisions, funding decisions, and working capital on business performance in small halal industries (IK) in Ternate. The respondents involved were 53 IK. This research is quantitative and descriptive. Data was collected using online questionnaires, namely, google forms and interviews. This study uses a simple random sampling technique in producing the research sample. The data analysis technique used multiple regression models and research hypothesis testing. The results showed that the financial literacy of IK owners was moderate and had no effect on business performance. Investment decisions of IK players are relatively good and do not affect business performance. The funding decisions of halal IK actors are rather good and impact business performance. The findings of this study are that working capital is classified as very good and has a positive and significant effect on IK business performance. Furthermore, working capital has a dominant impact on business performance, as seen from the bear value of the t table compared to 3 (three) other variables. This research implies that it can be used as a support for strategic decisions regarding the development of IK in the city of Ternate, that IK owners need to develop financial literacy, investment decisions, and appropriate funding decisions as well as manage the company's working capital effectively and efficiently so that the achievement of business performance is better.